(untitled) (Global Journal of Management and Business Research, 2016)
The study analyzed social networks and entrepreneurial orientation with particular reference to Network of African Student Entrepreneurs in Nigerian Universities. The objective was to explain the influence of social networks size on risk disposition among student entrepreneurs. extant literature based on the objective was reviewed. The theoretical underpinning is the sociological theory of entrepreneurship particularly the postulations of Frank Young 1971. The study adopted correlation descriptive method. ANOVA was used to analyze the data. A significant relationship was found to be existing between social networks size and risk disposition among student entrepreneurs. The implication of the result got is that if the students in Nigerian Universities fail to key into the revolution epitomized by the Network of African Student Entrepreneurs, then they run the risk of being bereft of entrepreneurial ideas.